Flow in a forward swept centrifugal fan - Mealing, B. E. (Cranfield University, 1988)
The original objective of this work, to improve the efficiency of a forward curved centrifugal fan, was redirected to the urgent solution of a serious impeller life problem arising under certain service conditions. Using a variety of experimental and theoretical techniques the flow pattern within the blade passage was analysed and the cause of the problem diagnosed. A new impeller has been designed and has been found to solve the service life problem while also yielding an improvement in efficiency. Because the project was carried out under the Total Technology programme the scope was widened to include consideration of the fan application in a suction roadsweeper : as a result of the wider technical and commercial investigation an opportunity has been identified for a new product offering benefits much greater than those sought within the scope of the original objective.